Effort of Multilevel Modeling in Organizational Research : CITIZENSHIP ORGANIZATIONAL BEHAVIOR AND WORK PERFORMANCE ON TASK, WITH SPIRITUAL LEADERSHIP PREDICTOR, WORK SPIRITUALITY CLIMATE, AND OPEN ORGANIZATIONAL CULTURE - Nilam Widyarini (Universitas Gunadarma, 2008)
Considering the hierarchy style in real organization, some theorists have been interested in finding the best way to measuring variable in order to fit with the concept, and also analyzing hierarchy data syle such as data in individual, group, and organizational level. The aim of this writing is to make a start as pioneer in multilevel research in Indonesia, especially in citizenship organizational behavior. The script of this research is preparing the model of employee work performance (individual level) such as citizenship organizational behavior and work performance with job unit level like spiritual leadership, open organizational culture, and spritual work climate as predictors.Key words: work performance, spiritual leadership, spiritual work climate, organizational culture, multilevel